Aggregation of full-length immunoglobulin light chains from systemic light chain amyloidosis (AL) patients is remodeled by epigallocatechin-3-gallate - Andrich, Kathrin; Hegenbart, Ute; Kimmich, Christoph; Schönland, Stefan (The journal of biological chemistry, 2017)
Intervention into amyloid deposition with anti-amyloid agents like the polyphenol epigallocatechin-3-gallate (EGCG) is emerging as an experimental secondary treatment strategy in systemic light chain amyloidosis (AL). In both AL and multiple myeloma (MM), soluble immunoglobulin light chains (LC) are produced by clonal plasma cells, but only in AL do they form amyloid deposits in vivo We investigated the amyloid formation of patient-derived LC and their susceptibility to EGCG in vitro to probe commonalities and systematic differences in their assembly mechanisms. We isolated nine LC from the urine of AL and MM patients. We quantified their thermodynamic stabilities and monitored their aggregation under physiological conditions by thioflavin T fluorescence, light scattering, SDS stability, and atomic force microscopy. LC from all patients formed amyloid-like aggregates, albeit with individually different kinetics. LC existed as dimers, ∼50% of which were linked by disulfide bridges. Our results suggest that cleavage into LC monomers is required for efficient amyloid formation. The kinetics of AL LC displayed a transition point in concentration dependence, which MM LC lacked. The lack of concentration dependence of MM LC aggregation kinetics suggests that conformational change of the light chain is rate-limiting for these proteins. Aggregation kinetics displayed two distinct phases, which corresponded to the formation of oligomers and amyloid fibrils, respectively. EGCG specifically inhibited the second aggregation phase and induced the formation of SDS-stable, non-amyloid LC aggregates. Our data suggest that EGCG intervention does not depend on the individual LC sequence and is similar to the mechanism observed for amyloid-β and α-synuclein.